Qualitative design of online reservation application for MSMEs - Piter Antonius; Saut Dohot Siregar (Institute of Accounting Research and Novation (IARN), 2025)
Digital transformation has become an essential requirement for Micro Small Medium Enterprises (MSMEs) in the culinary sector to face contemporary market competition. This research aims to explore the design and development process of online reservation applications that align with the specific characteristics of culinary MSMEs through a qualitative case study approach. The research methodology employs data triangulation through in-depth interviews, participatory observation, and document analysis involving culinary MSME owners, operational staff, and customers in the Bandung region. Research findings indicate that conventional reservation systems have significant limitations in terms of accuracy, efficiency, and information accessibility. Implementation of Progressive Web Apps-based applications with digital payment integration successfully improved operational efficiency by up to 60% and user satisfaction reached 88% based on the system usability scale. The findings confirm that adoption of online reservation technology provides transformational impact on culinary MSME business models, enhancing competitive advantage and customer retention rate by 18%. This research contributes to the development of sustainable and scalable digitalization framework for culinary MSMEs.